Assessment of the Exergy Performance of an Organosolv Process using Aspen Plus® - A. Mabrouk; X. Erdocia; M. González-Alriols; J. Labidi (Chemical Engineering Transactions, 2016)
Organosolv fractionation is a successful process to separate lignocellulosic biomass in its main component for the preparation of multiple products including biofuels, chemicals, and materials. In this study, the exergetic behaviour of the delignification process of olive tree pruning using ethanol-water as solvent media was evaluated. The experimental equipment consisted of several units, starting with a mixer, a heater, a reactor and, finally, a filtration step for the components separation. Exergetic analysis was used as the decision making tool for the evaluation of the global process efficiency by showing the sources of irreversibilities. The analysis was carried out with Aspen Plus®software. As a result, the total exergy losses found reached around98 kW, being the heater the main responsible of this quantity, contributing with about 28.75 % of the irreversibility generated in the studied sequence. The obtained information was used as the starting point for the optimization of the process operational conditions for a better energetic behaviour.